2015
DOI: 10.1007/s00380-015-0752-3
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of nicorandil on infarct myocardium in comparison with nitrate: assessed by cardiac magnetic resonance imaging

Abstract: In this pilot study, we compared the infarct and edema size in acute myocardial infarction (MI) patients treated by nicorandil with those treated by nitrate, using cardiac magnetic resonance (CMR) imaging. Fifty-two acute MI patients who underwent emergency percutaneous coronary intervention (PCI) were enrolled, and were assigned to receive nicorandil or nitrate at random just before reperfusion. For the assessment of infarct and edema areas, short-axis delayed enhancement (DE) and T2-weight (T2w) CMR images w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 33 publications
1
26
0
2
Order By: Relevance
“…This finding is in contrary to those found in the most of previous studies where the drug was used through either intravenous or intracoronary route. [6][7][8][9]13,14 Also, in the present study, oral nicorandil did not have any effect on infarct size reduction and left ventricular function as evident by similar peak cardiac troponin and left ventricular ejection fraction (Table 1) . These findings are consistent with those reported by Kitakaze et al, who showed the intravenous nicorandil with no effect on either infarct size or left ventricular function.…”
Section: Discussionsupporting
confidence: 60%
“…This finding is in contrary to those found in the most of previous studies where the drug was used through either intravenous or intracoronary route. [6][7][8][9]13,14 Also, in the present study, oral nicorandil did not have any effect on infarct size reduction and left ventricular function as evident by similar peak cardiac troponin and left ventricular ejection fraction (Table 1) . These findings are consistent with those reported by Kitakaze et al, who showed the intravenous nicorandil with no effect on either infarct size or left ventricular function.…”
Section: Discussionsupporting
confidence: 60%
“…Unexpectedly, nicorandil could not decrease the IS assessed by creatine kinase compared to the placebo. Another small study performed by Yamada et al (16) enrolled 55 patients with AMI undergoing pPCI and administered intracoronary nicorandil or nitrate for 4 days. Their data revealed that nicorandil reduced IS by 18.9% compared with nitrate.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is still controversial whether nicorandil diminishes IS in patients with acute myocardial infarct (15). Indeed, nicorandil was mostly administered a short time before PCI or during the perioperative period in previous trials (15, 16). However, microvascular obstruction would still deteriorate continuously after pPCI, and myocardial stunning may require several days or weeks to recover (10, 17).…”
Section: Introductionmentioning
confidence: 99%
“…Seven of the thirteen studies assessed the post PCI TIMI flow grade in each of the study groups (Kitakaze M 9,13,14,16,18,21,22 Meta-analysis of this particular outcome showed that there was a significant difference in the TIMI flow grade between the Nicorandil and control groups. This was similar to the earlier two metaanalysis (Wu M et al and Iwakura K et al) 8,23 that clearly showed the superiority of Nicorandil over control in improving the post-PCI TIMI flow grade.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the characteristics that were not reported in the baseline data could play a strong confounding role in influencing the outcome. For example, (Yamada K et al) 14 did not report the baseline CMR imaging between the groups. Although, small operator experience could also have a considerable impact on the outcomes.…”
Section: Discussionmentioning
confidence: 99%